Bilaterale akute syphilitische posteriore plakoide Chorioretinopathie (ASPPC): Angiographie- und Autofluoreszenz-Merkmale - Bellmann, Caren; Holz, Frank G.; Breitbart, Andreas; Völcker, Hans Eberhard (Der Ophthalmologe, 1999)
Acute syphilitic posterior placoid chorioretinitis (ASPPC) has been described as a rare chorioretinal manifestation in patients with secondary syphilis. The fundus changes may simulate other chorioretinal disorders and thus delay an accurate diagnosis and initiation of appropriate pharmacological therapy.
Englische Zusammenfassung: Bilateral acute syphilitic posterior placoid chorioretinopathy - angiographic and autofluorescence characteristics
Gesehen am 02.03.2021